Investigations on the driving forces of the fluorocarbon surfactant-assisted spontaneous imbibition using thermogravimetric analysis (TGA). Issue 67 (14th November 2018) - Chen, Haihui; Fan, Hongfu; Zhang, Yi; Xu, Xingguang; Liu, Long; Hou, Qingfeng
Abstract : A new method using TGA was applied to study the predominant driving force and controlling factors of fluorocarbon surfactant-assisted spontaneous imbibition. Abstract : Spontaneous imbibition is crucial for the development of matrix-fractured petroleum reservoirs. To improve the ultimate oil recovery, it is essential to demonstrate the role of the surfactant solution on the imbibition process. In this study, spontaneous imbibition experiments were carried out using self-prepared oil sand that to investigate the dependence of oil recovery on the concentration of a fluorocarbon surfactant (FS-30). Emulsion and solubilization were assessed to identify the correlation between oil-water interface properties and spontaneous imbibition. Moreover, thermogravimetric analysis (TGA) was also applied to accurately determine the imbibition recovery and look into the influence of components of crude oil on spontaneous imbibition. The maximum ultimate oil recovery in this work was 70.8% using 0.3 wt% FS-30, when the oil-solid adhesion tension, the capillary pressure ( P C ) and solubilization factor ( S F ) attained extreme values of −3.7002 mN m −1, 4.8751 MPa and 242.7 mL g −1, respectively. It was found that the surface activator played a critical role in promoting the imbibition process through altering the contact angle and interfacial tension. A negative adhesive tension and a positive capillary pressure would accordingly be generated, which facilitated the departure of oil droplets from the rock surface. In addition, it was observed that a lower solubilization factor and higher emulsion stability could favour spontaneous imbibition. Finally, heavier components in oil sands were more prone to be displaced than lighter counterparts, especially when the surfactant concentration was relatively high. This study may shed light on the effect of surfactants on spontaneous imbibition and thus is of great significance in understanding the underlying mechanism of the imbibition process.